Linear interpolation based controller design for trajectory tracking under uncertainties: Application to mobile robots. (December 2015) - Scaglia, Gustavo; Serrano, Emanuel; Rosales, Andrés; Albertos, Pedro
Abstract: The problem of trajectory tracking control in mobile robots under uncertainties is addressed in this paper. Following the results of mobile robots trajectory tracking reported in (Scaglia et al., 2010 ), the problem of model errors is focused and the zero convergence of tracking errors under polynomial uncertainties is demonstrated. A simple scheme is obtained, which can be easily implemented. Simulation and experimental results are presented and discussed, showing the good performance of the controller. Highlights: The trajectory tracking control in mobile robots under uncertainties is addressed. The controller design for trajectory tracking is based on linear algebra. The approach is applied in a nonlinear system with additive uncertainty. Zero convergence of tracking error under polynomial uncertainties is demonstrated. Several experiments were performed by using a PIONEER 3AT mobile robot.